Understanding “Childhood Poly-Victimization” to help uncover abuse during child investigative interviewing: a systematic review - Morlat, Pantxika Victoire; Alison, Laurence (Frontiers in Psychology, 2024)
It is well established that child victims are some of the most challenging populations to interview. Indeed, children tend to feel ashamed, scared or in denial, leading to difficulties for law enforcement when gathering information, and subsequently with prosecuting offenders. Moreover, crimes against children increasing, it is common for interviewed victims to have experienced several abuses (poly-victimization). Thus, the main goals of this study are to (1) identify the facets that are included in poly-victimization, in order to (2) provide a clear definition that can be used by law enforcement during child interviews, which could lead to (3) a better identification of cases of abuse to maximize safeguarding and protect children.A systematic review was used to establish the differences in conceptualizations of poly-victimization as well as the measurements chosen by research to measure this concept. The current systematic review included research articles on childhood poly-victimization using a quantitative measuring instrument published as of 2007, that focused on populations under 18 years of age.The findings were divided into 1) conceptual dimensions, 2) characteristics of study's population and 3) measures and psychometrics properties. It was found that research used various terms for poly-victimization, yet with numerous definitions implying differences in number of abuses, time frame and mental health aspects to be considered in the identification of poly-victimization. The included papers (n = 6) were from Europe, Asia, and North America. Half of the studies used the Juvenile Victimization Questionnaire (JVQ; Finkelhor et al., 2005) but adapted either i) to the study's population, ii) possible answers, iii) wording of questions or iv) by removal of questions.Conclusions: Our findings highlight the need for a more theoretically coherent definition of childhood poly-victimization. Questions regarding number of abuses, time consideration (past year vs. lifetime), mental health and severity of abuse should be addressed to develop a unified definition of polyvictimization. Rapport-based interviews should be the focus to uncover the truth and to avoid a secondary trauma in the crisis of a child's disclosure of abuse. The authors propose a 'Decision Tree for Identifying Childhood Poly-Victimization' designed to be used by law enforcement during child investigative interviews.